2012
DOI: 10.1186/ar3695
|View full text |Cite
|
Sign up to set email alerts
|

Tight regulation of wingless-type signaling in the articular cartilage - subchondral bone biomechanical unit: transcriptomics in Frzb-knockout mice

Abstract: IntroductionThe aim of this research was to study molecular changes in the articular cartilage and subchondral bone of the tibial plateau from mice deficient in frizzled-related protein (Frzb) compared to wild-type mice by transcriptome analysis.MethodsGene-expression analysis of the articular cartilage and subchondral bone of three wild-type and three Frzb-/- mice was performed by microarray. Data from three wild-type and two Frzb-/- samples could be used for pathway analysis of differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 51 publications
(61 reference statements)
7
25
0
1
Order By: Relevance
“…Lories et al [73] reported that the genetic association between osteoarthritis and FRZB polymorphisms is corroborated by increased cartilage proteoglycan loss in models of arthritis in Frzb(−/−) mice and loss of Frzb may contribute to cartilage damage by increasing the expression and activity of Mmps, in a Wnt-dependent and Wnt-independent manner. Consistent with this finding, Frzb knockout mice are more sensitive to chemical-induced OA [74]. …”
Section: Molecular Mechanisms Related To Oa Pathogenesismentioning
confidence: 54%
“…Lories et al [73] reported that the genetic association between osteoarthritis and FRZB polymorphisms is corroborated by increased cartilage proteoglycan loss in models of arthritis in Frzb(−/−) mice and loss of Frzb may contribute to cartilage damage by increasing the expression and activity of Mmps, in a Wnt-dependent and Wnt-independent manner. Consistent with this finding, Frzb knockout mice are more sensitive to chemical-induced OA [74]. …”
Section: Molecular Mechanisms Related To Oa Pathogenesismentioning
confidence: 54%
“…Moreover, protein secreted Frizzledrelated protein (Sfrp)3, a secreted negative regulatory factor of Wnt signaling, and mutations of the Frizzledrelated protein (FrzB) gene can increase susceptibility to OA (35). FrzB knockout mice are susceptible to chemical-induced OA (36). Furthermore, overexpression of Wnt-induced signaling protein 1 (WISP-1) in the mouse knee joint also leads to cartilage impairment.…”
Section: Effect Of Tgf-β In Articular Chondrocyte Degeneration In Oamentioning
confidence: 98%
“…Indeed, transcriptomic analysis of the cartilage–subchondral bone unit in Frzb −/− mice revealed compensatory upregulation of other sFRPs, confirming that Wnt signalling in these tissues is tightly regulated. 64 …”
Section: Wnts and Oa: A Challenging Networkmentioning
confidence: 99%